Safety and Preliminary Efficacy of a Novel Host-Modulatory Therapy for Reducing Gingival Inflammation - Hasturk, Hatice; Schulte, Fabian; Martins, Melissa; Sherzai, Homa; Floros, Constantinos; Cugini, MaryAnn; Chiu, Chung-Jung; Hardt, Markus; Van Dyke, Thomas (Frontiers in Immunology, 2021)
Background. Periodontal disease is among the sixth most common inflammatory diseases worldwide with high risk to promote complications from other inflammatory diseases including diabetes, cardiovascular disease and Alzheimer’s Disease. Failure of active resolution of inflammation pathways is implicated in pathogenesis of periodontal diseases, including gingivitis. Lipoxin A4 (LXA4), a member of the specialized pro-resolving lipid mediators (SPMs) that drive resolution of inflammation via GPC-receptor mediated pathways, offered therapeutic advantages in preclinical models of periodontitis. Methods. We conducted a randomized, placebo-controlled, parallel-group Phase 1 clinical trial to determine the safety and preliminary efficacy of an LXA4 analog in patients with gingival inflammation. One hundred twenty-seven (127) individuals were randomized to daily use of an oral rinse containing a LXA4 mimetic, methyl ester-benzo-lipoxin A4 (BLXA4), placebo rinse or a no-rinse control group for 28 days. Treatment emergent adverse events (TEAEs) were assessed for safety, the primary outcome. Secondary outcomes included the change in the level of gingival inflammation and periodontal pocket depth (PD). Serum SPMs were monitored using targeted lipid mediator lipidomics to assess potential systemic impact of BLXA4. Results. The frequency of TEAEs was similar in BLXA4 and placebo-treated groups with no study-related serious adverse events. Once-daily rinsing with BLXA4 for 28-days resulted in a greater decrease in gingival inflammation compared to placebo rinse and no-rinse control groups (mean change: 0.26 GI unit vs 0.21 and 0.17, respectively). PD reduction was also greater with BLXA4 oral rinse compared to placebo and no-rinse groups (mean reduction: 1.23 mm vs. 0.71 mm and 0.46 mm, respectively). Topical application of BLXA4 increased serum SPMs. Conclusion. Treatment with BLXA4 reduces local inflammation, and increases pro-resolution molecules systemically, which may dampen inflammation that can mediate progression and course of inflammatory diseases beyond periodontitis. Trial Registration. ClinicalTrials.gov NCT02342691.